Improvement in mechanical properties of structural AZ91 magnesium alloy processed by friction stir processing. (31st October 2022) - Tripathi, Hariom; Bharti, Ajaya; Saxena, Kuldeep K.; Kumar, Naveen
ABSTRACT: The purpose of this study is to observe the change in the microstructure of the magnesium AZ91 alloy with the help of refinement of the grain structure due to Friction Stir Processing (FSP), resulting in to a change of mechanical behaviour. During FSP, effect of the variation of tool rotational speed was also investigated. The microstructural and mechanical behaviour of the prepared samples before and after FSP were investigated with the help of X-Ray Diffraction (XRD), Optical Microscopy (OM), Scanning Electron Microscopy (SEM), Microhardness test and Tensile test. The base initial material's (Magnesium Alloy AZ91 grade) microstructure consists of irregularly distributed secondary phases (Al12 Mg17 ) along the grain boundaries and within the grains, while the FS Processed samples show the regular and uniform grains with the dissolution of the secondary phase. The improvement in the hardness and tensile strength was observed after Friction Stir processing of the samples' with the variation of Tool rotational speed. The Ultimate Tensile Strength (UTS) and percentage elongation of samples processed at 1160 rpm were increased by approximately 56% and 118% as compared to the base material.